Association between Parkinson's Disease and Helicobacter Pylori - OĞUZ, SIDIKA (KOREAN NEUROLOGICAL ASSOC, 2016)
Helicobacter pylori (HP) is a common infection of the gastrointestinal system that is usually related to peptic ulcers. However, recent studies have revealed relationships between HP and many other diseases. Although the exact mechanism is unknown, HP can prevent the absorption of certain drugs. A high prevalence of HP has been found in patients with Parkinson's disease, and this bacterium causes motor fluctuations by affecting the absorption of levodopa, which is the main drug used to treat Parkinson's disease. Eradicating HP from patients with Parkinson's disease by applying antibiotic treatment will increase the absorption of levodopa and decrease their motor fluctuations.
Keywords: Parkinson's disease; Helicobacter pylori; levodopa; motor fluctuations; INTESTINAL BACTERIAL OVERGROWTH; L-DOPA ABSORPTION; IDIOPATHIC PARKINSONISM; MOTOR FLUCTUATIONS; NONMOTOR SYMPTOMS; GASTROINTESTINAL-TRACT; CHRONIC INFECTION; ERADICATION; MANIFESTATIONS; SURVEILLANCE